Investigação microestrutural e estudo das propriedades mecânicas da liga de alumínio AA2139 T3 e T8 soldadas por Friction Stir Welding - FSW - Saccon, Vinícius Toledo (2011)
Aluminum alloys have low density and high corrosion resistance, and because of that this alloys are being increasingly used in aircraft industry. However, a downside of this alloys is its weldability in fusion process, which can generate defects such as H2`s porosity and formation of high temperatures cracks limiting its applicability. Seeking an alternative process, it was developed a solid state welding process called Friction Stir Welding - FSW. The main advantage of this process is that welding occurs at a temperature below the melting temperature of the material, eliminating defects from solidification. Since its invention, the FSW gets world attention, because structural alloys with difficult weldability showed excellent results metallurgical and mechanical after welding. Therefore, in this study the aluminum alloy AA2139 was welded by FSW, a structural alloy with a high potential for aerospace applications due to good combination of strength and fatigue and fracture toughness. Thus, it was evaluated the mechanical and metallurgical behavior of aluminum alloy AA2139 under different conditions of heat treatment, T3 and T8. The microstructural features were investigated using optical and electron microscopy (SEM and TEM) as well as the mechanical behavior was determined by bending testing, microhardness profiles, conventional tensile testing (including system analysis of deformation - ARAMIS) and tensile testing using micro-samples and also the temperature measurements were performed during welding. The results showed that welds in alloy AA2139-T3 and AA2139-T8 may show different results, even using the same tool and the same welding parameters. Moreover, the temperature reached during welding affects the precipitation in the welded region which determines the performance of the weld.